Harmful effects of carbamazepine on the postnatal development of the rat ventral prostate - Oliva, Samara U.; Scarano, Wellerson R. [UNESP]; Okada, Fatima K.; Miraglia, Sandra M. (Biomed Central Ltd., 2012)
Background: Carbamazepine (CBZ) is a first-line antiepileptic drug (AED), although it is also used for the treatments of psychiatric disorders and neuropathic pain. The CBZ utilization has been associated with male reproductive damage, including hormonal alterations, sexual dysfunction and reduction of sperm quality. The wide and long-term use of the CBZ is a common schedule in children and adolescents and alters the testosterone level in adult rats and humans. The objective of this work was to evaluate the CBZ side effects on the ventral prostate of rats from pre-puberty to sexual maturation, since the prostate is an androgen-dependent organ.Methods: Twenty three day-old male albino Wistar rats received CBZ diluted in propylene glycol (20 mg/Kg/i.p via). The treatment lasted 20, 40 and 70 days, according to the different stages of the rat sexual maturation. At the end of each treatment period, ventral prostates were removed and histologically processed. The prostate sections were submitted to the histopathological, morphological and stereological analyses using image analysis system.Results: Reductions of the glandular epithelium, glandular lumen and fibromuscular stroma volume of the ventral prostate were observed in adult rats treated with CBZ since the weaning. Triggering and degranulation of mast cells were observed in the fibromuscular stroma of prepubertal and pubertal CBZ treated rats.Conclusions: The results suggest a direct effect of the CBZ on rat ventral prostate, evidenced by increase of mast cell and macrophage populations during pre-puberty and puberty causing a ventral prostate accentuated damage in the adult phase.
Keywords: Carbamazepine; Ventral prostate; Mast cells; Stereology